Near-real-time welfare and livelihood impacts of an active civil war: Evidence from Ethiopia - Abay, Kibrom A.; Tafere, Kibrom; Berhane, Guush; Chamberlin, Jordan; Abay, Mehari Hiluf (International Food Policy Research Institute, 2022)
Ethiopia is currently embroiled in a large-scale civil war that has continued for more than a year. Using unique High-Frequency Phone Survey (HFPS) data, which spans several months before and after the outbreak of the war, this paper provides fresh evidence on the ex durante impacts of the conflict on the food security and livelihood activities of affected households. We use difference-in-differences estimation to compare trends in the outcomes of interest across affected and unaffected regions (households) and before and after the outbreak of the civil war. Seven months into the conflict, we find that the outbreak of the civil war increased the probability of moderate to severe food insecurity by 38 percentage points. Using the Armed Conflict Location and Event Data (ACLED) on households’ exposure to violent conflict, we show that exposure to one additional battle leads to 1 percentage point increase in the probability of moderate to severe food insecurity. The conflict has reduced households’ access to food through supply chain disruptions while also curtailing non-farm livelihood activities. Non-farm and wage related activities were the most affected by the conflict while farming activities were relatively more resilient. Similarly, economic activities in urban areas were much more affected than those in rural areas. These substantial impact estimates, which are likely to be underestimates of the true average effects on the population, constitute novel evidence on the near-real-time impacts of an on-going civil conflict, providing direct evidence on how violent conflict disrupts the functioning of market supply chains and livelihoods activities. Our work highlights the potential of HFPS to monitor active and large-scale conflicts, especially in contexts where conventional data sources are not immediately available.